ATR Kinase Activation Mediated by MutSα and MutLα in Response to Cytotoxic O(6)-Methylguanine Adducts - Yoshioka, Ken-ichi (2006)
S(N)1-type alkylating agents that produce cytotoxic O(6)-methyl-G (O(6)-meG) DNA adducts induce cell cycle arrest and apoptosis in a manner requiring the DNA mismatch repair (MMR) proteins MutSα and MutLα. Here, we show that checkpoint signaling in response to DNA methylation occurs during S phase and requires DNA replication that gives rise to O(6)-meG/T mispairs. DNA binding studies reveal that MutSα specifically recognizes O(6)-meG/T mispairs, but not O(6)-meG/C. In an in vitro assay, ATR-ATRIP, but not RPA, is preferentially recruited to O(6)-meG/T mismatches in a MutSαand MutLα-dependent manner. Furthermore, ATR kinase is activated to phosphorylate Chk1 in the presence of O(6)-meG/T mispairs and MMR proteins. These results suggest that MMR proteins can act as direct sensors of methylation damage and help recruit ATR-ATRIP to sites of cytotoxic O(6)-meG adducts to initiate ATR checkpoint signaling.